Improving Work Motivation of Nutrition Implementers in Health Centers: Analysis of the Influence of Work Experience, Competence, and Rewards - Fauzie Rahman; Syamsul Arifin; Meitria Syahadatina Noor; Husaini Husaini; Rosihan Adhani; Muhammad Abdan Shadiqi; Neka Erlyani; Muhamad Muslim; Ifa Hafifah; Ha Thi Thu Trang (Faculty of Public Health, Hasanuddin University, Makassar, 2024)
Success in addressing nutritional problems can be achieved when nutrition implementers possess strong abilities and skills in executing nutritional service program activities at community health centers. High work motivation among nutrition implementers significantly contributes to the successful implementation of these programs. This study aims to analyze the influence of work experience, competence, and reward provision on the work motivation of nutrition implementers. This research employs a quantitative approach with a cross-sectional design. The population consists of all nutrition implementers in South Kalimantan Community Health Centers' work area in Indonesia. A sample of 253 respondents was selected using purposive sampling. The research instrument utilized was a questionnaire, and data analysis involved simple linear regression analysis. The findings indicate a significant effect of work experience on work motivation, with a significance value of .00 < .05. However, competence does not have a significant impact on work motivation, as its significance value is .098 > .05. Similarly, reward provision does not significantly influence work motivation, with a significance value of .439 > .05. In conclusion, work experience significantly affects the work motivation of nutrition implementers. Therefore, efforts to enhance the motivation of nutrition implementers are essential, as they will ultimately improve the effectiveness of nutrition service programs in health centers, contributing to the prevention of stunting and the overall enhancement of public health.